?m-STATISTICAL CONVERGENCE OF ORDER (?)over-tilde FOR DOUBLE SEQUENCES OF FUNCTIONS - Cinar, Muhammed; Et, Mikail (Univ Nis, 2020)
In this paper, we have introduced and examined the concepts of Delta(m)-pointwise and Delta(m)-uniform statistical convergence of order (alpha) over tilde for double sequences of real valued functions. Also, we have given the concept of Delta(m)-statistically Cauchy sequence for double sequences of real valued functions and proven that it is equivalent to Delta(m)-pointwise statistical convergence of order (alpha) over tilde for double sequences of real valued functions. Some relations between S-(alpha) over tilde(2) (Delta(m), f)-statistical convergence and strong [w(p)(2)]((alpha) over tilde) (Delta(m), f) -summability have also been given.
Keywords: Statistical convergence; Cauchy sequence; summability